What Matters most for museums? Individual and social influences on employees' innovative behaviour. (3rd March 2020) - Goulaptsi, Ioanna; Manolika, Maria; Tsourvakas, George
ABSTRACT: Although prior research has discussed the effects of several determinants on individual innovativeness, little is known about how individual together with social processes impact the adoption of innovation by employees. To address this issue and to examine the mediating mechanisms through which transformational leaders influence innovative behaviour, 200 museum employees were asked to fill out the Individual Innovativeness Scale, the Team Climate Inventory, and the Multifactor Leadership Questionnaire, as well as to provide their demographic data. The multiple regression analysis revealed that individuals' demographics, transformational style of leadership, and task orientation are essential to explain museum employees' innovativeness. Additionally, task orientation partially mediated the association between transformational leadership style and individual innovation. These findings not only provide a valuable basis for better understanding museum employees' acceptance of innovation, but also put forward the need to consider various variables on the promotion of employees' innovative behaviour within art organizations.